2018
DOI: 10.7567/jjap.57.07le12
|View full text |Cite
|
Sign up to set email alerts
|

Welding characteristics of Cu and Al plates using planar vibration by a dumbbell-shaped ultrasonic complex vibration source

Abstract: Conventional ultrasonic welding uses vibrations with a one-dimensional linear locus. Because the vibration energy is small, this method suffers from the drawbacks that the weld strength is low and variable depending on the installation direction of the welding sample. Our previous studies have revealed that the weld strength can be improved by using vibrations with a two-dimensional planar locus. However, the question of whether welding using planar vibration could be achieved in a short weld time and the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…In our previous work, we confirmed that the amplitude amplification factors of the torsional angular velocity and torsional vibration displacement amplitude of up to 4.8 and 3.5, respectively, could be used for ultrasonic metal welding. [8][9][10] In the present work, we focus on a stepped horn with d 2 of 22.0 mm, which has amplitude amplification factors of the torsional angular velocity and torsional vibration displacement amplitude of 4.8 and 3.5, respectively, and we measure the vibration characteristics experimentally in a stepped horn configured as a vibration source, as shown in Fig. 1.…”
Section: Fem Analysis Of a Stepped Horn With A Hollow Partmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous work, we confirmed that the amplitude amplification factors of the torsional angular velocity and torsional vibration displacement amplitude of up to 4.8 and 3.5, respectively, could be used for ultrasonic metal welding. [8][9][10] In the present work, we focus on a stepped horn with d 2 of 22.0 mm, which has amplitude amplification factors of the torsional angular velocity and torsional vibration displacement amplitude of 4.8 and 3.5, respectively, and we measure the vibration characteristics experimentally in a stepped horn configured as a vibration source, as shown in Fig. 1.…”
Section: Fem Analysis Of a Stepped Horn With A Hollow Partmentioning
confidence: 99%
“…[1][2][3] Recently, studies have examined various desirable techniques, such as complex vibration welding, laser combination welding, and resinmetal welding. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] In addition, we have proposed an ultrasonic welding technique for complex vibration welding that uses a combination of longitudinal and torsional vibrations of frequencies to form a planar locus. [7][8][9][10][11][12][13] The ultrasonic vibration source is important for this type of ultrasonic welding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors have proposed an ultrasonic welding technique of using planar vibration composed of longitudinal and torsional vibrations to apply two-dimensional stress [15]. The authors focused on the tensile shear strength, which indicates the breaking strength when a shear load is applied parallel to the weld in a welded material, using an aluminum plate for the upper weld part and a copper plate for the lower weld part, and demonstrated that welding using planar vibration results in higher strength in a shorter time than welding using conventional linear vibration [16]. However, the load that occurs in many industrial products is not only shear load but also peel load that is applied in a direction perpendicular to the weld surface.…”
Section: Introductionmentioning
confidence: 99%
“…Miura et al investigated welding using a dumbbell vibration source with longitudinal and torsional vibrators that generate two-dimensional planar vibration displacements [12][13][14].…”
Section: Introductionmentioning
confidence: 99%